Can intuitive eating work at work? A qualitative dive into workplace wellness programs - McMahon, Katie, author; Graham, Dan, advisor; Stotz, Sarah, committee member; French, Kimberly, committee member; Shomaker, Lauren, committee member (Colorado State University. Libraries, 2025)
Background: Workplace wellness programs have traditionally emphasized weight-loss outcomes; however, evidence supporting the long-term efficacy of such programs is limited, and research has documented adverse consequences, including increased long-term weight gain, heightened weight stigma in the workplace, and elevated stress and binge-eating behaviors. Intuitive eating (IE), an approach emphasizing attunement to physiological hunger and satiety cues alongside principles of gentle nutrition, has emerged as a promising alternative to weight-centric interventions. Preliminary workplace-based intuitive eating interventions have demonstrated improvements in employees' dietary quality, reductions in disordered eating behaviors, and decreased internalization of weight stigma. Purpose: This exploratory study examined workplace wellness programs from the perspectives of nutrition experts and organizational wellness managers to understand the factors limiting the adoption of IE as a workplace healthy eating initiative. The research investigated how existing wellness programs were selected, developed, implemented, and evaluated, with particular attention to the integration of IE principles. By exploring facilitators and barriers to incorporating IE, as well as organizational conceptualizations of ideal initiatives, the study aimed to inform pathways for developing, implementing, and marketing IE-based workplace wellness initiatives. Methods: To address the research questions, 16 semi-structured interviews were conducted via Microsoft Teams with 9 corporate nutrition experts and 7 wellness managers during the fall of 2024. Given the specialized nature of the participant population, purposive maximum variation sampling and snowball sampling techniques were employed. Interviews continued until data saturation was achieved. All transcripts were coded using both deductive and inductive approaches in Atlas.ti software and analyzed using thematic analysis. Results: Two major themes and 12 subthemes emerged, capturing the direct and indirect influences on IE implementation in workplace wellness programs. Theme one revolved around direct influences and included facilitators such as positive attitudes from nutrition experts, recognition of harms associated with weight loss initiatives, and the use of diverse implementation strategies. Barriers included limited knowledge and training in IE affecting organizational buy-in, cultural resistance to IE from dominant diet norms, stigma within the IE community, and the prioritization of perceived cost savings. Theme two centered on indirect influences and encompassed organizational-level barriers, including productivity concerns, superficial and unsustainable program outcomes, and employing unstandardized or no evaluation methods, while a facilitator to IE is the movement toward more holistic approaches to wellness initiatives. Opportunities for advancing IE programming included framing IE as a mental health benefit to enhance organizational appeal and offering group-based and hybrid program formats. Conclusions: Results from this study indicate some differing opinions from nutrition experts and wellness managers. Nutrition experts advocate for a weight-inclusive approach that prioritizes health behaviors and equitable care across the weight spectrum while wellness managers may be open to IE programming with enhanced awareness of IE benefits and increased critical evaluation of weight-based programs.
Keywords: health promotion; workplace wellness; intuitive eating; eating behaviors